Current View on the Problem of Treatment for Cystic Echinococcosis of the Liver - V. S. Boyarinov; S. V. Novikov; M. L. Rogal; P. A. Yartsev (Неотложная медицинская помощь)
Echinococcosis of the liver is an important problem of hematology, which in many cases is solved only with the help of surgical methods of treatment. This is primarily due to the significant number of patients with cystic echinococcosis of the liver in endemic regions, despite the implementation of preventive measures. There are still many complicated and unsolved questions concerning differential diagnostics and choice of tactics of surgical treatment for liver echinococcosis.The problem of surgical treatment of liver echinococcosis is far from its final solution. Depending on the size of the liver lesion area, the nature of the process, severity and type of complications, different forms of treatment for cystic echinococcosis of the liver are chosen. However, during surgical treatment, such complications as liver failure, massive intraoperative bleeding with the development of hemorrhagic shock may develop. After surgical interventions for cystic echinococcosis of the liver, morphologic changes in liver tissues and signs of liver failure do not disappear, but progress; and this negatively affects the longterm treatment outcomes. Therefore, reduction of traumatic operations, prevention of hemorrhagic complications, maximum preservation of functioning liver parenchyma is one of the most important directions of echinococcosis surgery development.In this paper, we analyze the literature sources of PubMed, eLibrary, RINC databases, which are devoted to the comparison of the effectiveness of methods of surgical treatment for cystic echinococcosis of the liver, published for the last 5 years. The conducted analysis of modern literature testifies to the relevance of the problem of choosing the method of surgical treatment for liver echinococcosis.In recent years, there has been intensive development of surgical hepatology, which is associated with the introduction of new technologies in the diagnosis and treatment of patients with various focal liver diseases, including cystic echinococcosis. At the same time at present, there are great differences in surgical indications for treatment of hepatic echinococcosis due to differences in the technical level and experience in conducting or mastering these techniques.